2022
DOI: 10.3390/pharmaceutics14010123
|View full text |Cite
|
Sign up to set email alerts
|

Oral Immunogenicity of Enterotoxigenic Escherichia coli Outer Membrane Vesicles Encapsulated into Zein Nanoparticles Coated with a Gantrez® AN–Mannosamine Polymer Conjugate

Abstract: Enterotoxigenic Escherichia coli (ETEC) represents a major cause of morbidity and mortality in the human population. In particular, ETEC infections affect children under the age of five from low-middle income countries. However, there is no licensed vaccine against this pathogen. ETEC vaccine development is challenging since this pathotype expresses a wide variety of antigenically diverse virulence factors whose genes can be modified due to ETEC genetic plasticity. To overcome this challenge, we propose the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The use of PET imaging allows qualitative and quantitative visualization of the presence of radiometabolites and free radioisotopes through radiotracers while offering the advantage of high sensitivity and noninvasive ( Patel et al., 2022 ). Berzosa et al attempted to develop radioisotope-labeled OMVs to assess biodistribution, but they only showed in-vitro biodistribution over 10 h, which was related to a 99 m Tc half-life of only 6 h ( Berzosa et al., 2022 ). Jang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of PET imaging allows qualitative and quantitative visualization of the presence of radiometabolites and free radioisotopes through radiotracers while offering the advantage of high sensitivity and noninvasive ( Patel et al., 2022 ). Berzosa et al attempted to develop radioisotope-labeled OMVs to assess biodistribution, but they only showed in-vitro biodistribution over 10 h, which was related to a 99 m Tc half-life of only 6 h ( Berzosa et al., 2022 ). Jang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of single photon emission computed tomography ( SPECT ) based detection of radioisotope-labeled OMVs has been used for in vivo tracing of OMVs of bacterial pathogens ( Berzosa et al., 2022 ). The technique of SPECT has excellent sensitivity for deep tissue imaging and allows quantitative measurements but is not superior in terms of spatial resolution and imaging time ( Choi et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oral immunization was more convenient than injection, but it is susceptible to loss and can lead to unstable immunological effects. Previous studies have demonstrated that outer membrane vesicles (OMVs) from E. coli encapsulated into Zein Nanoparticles coated with a Gantrez ® AN–Mannosamine Polymer Conjugate elicited high levels of IgG antibodies, while oral administration of the outer membrane protein alone did not elicit an antibody response ( 43 ). In contrast, displaying CD0873 on liposomes without encapsulation elicited significantly different IgG and IgA titers from the control group after three oral immunizations ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an OMV conjugated with a nanomaterial was shown to be highly effective against ETEC [165]. Also, in an investigation by Blackwood et al [166], a whole‐cell vaccine administered intranasally in a mice model reduced bacterial load and protected the mice against P. aeruginosa and B. pertussis .…”
Section: The Potential Contribution Of Different Emerging Approaches ...mentioning
confidence: 99%